(untitled) (Modern education and development, 2025)
This article investigates the impact of Project-Based Learning (PBL) on developing critical thinking and collaborative skills among secondary school students. In contrast to traditional methods, PBL encourages learners to explore real-world problems through student-centered inquiry and teamwork. Using a mixed-methods research design, the study explores how integrating PBL improves cognitive engagement, problem-solving abilities, and interpersonal cooperation. Findings reveal that students engaged in project-based tasks demonstrate greater ownership of their learning process and perform better in analytical and team-based tasks. The article provides practical recommendations for educators seeking to implement PBL as a strategic instructional method aligned with 21st-century learning goals.